2021
DOI: 10.1002/chem.202005437
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Ambiphilic Reactivity of Metalated Diorgano‐Phosphonite Boranes

Abstract: Unprecedented metalated phosphonite boranes were prepared from PH-substituted precursors and silyl amides. Althoughp otassium derivatives were thermally stable and could even be isolated and structurally characterised,l ithiated analogues proved to be unstable towards self-condensation under cleavage of LiOR at ambient temperature. Reaction studies revealed that the metalated phosphonite boranes exhibit ambiphilic character. Their synthetic potential as nucleophilic building blocks was demonstrated in the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Borane adducts of phosphides with N‐ or O‐based substituents ( I a , b , Scheme 1) [1,2] were recently introduced as complements to diorganophosphides ( II ), which are well‐known as synthetically valuable phosphorus‐based nucleophiles [3] . The possibility to couple I with suitable electrophiles and then remove the protecting borane from the product permits using these species in a similar manner as conventional phosphides as synthetic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Borane adducts of phosphides with N‐ or O‐based substituents ( I a , b , Scheme 1) [1,2] were recently introduced as complements to diorganophosphides ( II ), which are well‐known as synthetically valuable phosphorus‐based nucleophiles [3] . The possibility to couple I with suitable electrophiles and then remove the protecting borane from the product permits using these species in a similar manner as conventional phosphides as synthetic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[2] We have recently shown that borane coordination can be used to overcome the notorious reluctance of secondary diaminophosphines Ia and phosphonites IIa (Scheme 1) to undergo metalation at their PH-bond and enables the forthright generation of thermally stable -and in some cases even isolable -phosphide boranes Ib and IIb, respectively. [3] [4] Such species, which had previously only been described as elusive intermediates, [5] make attractive synthetic tools that can serve, like the traditional PHor P(SiR 3 )-substituted phosphides (IIIb, IVb), as nucleophilic building blocks for the synthesis of functional phosphines. [6] However, whereas the products formed by quenching IIIb/IVb with electrophiles retain nucleophilic character at phosphorus (implying that further derivatization requires as well electrophilic reagents), the substituents in Ib/IIb impose electrophilic character on the P-atom in a resulting phosphine and make Ib/ IIb reagents that can decorate an electrophilic substrate with an electrophilic R 2 P-fragment allowing for post-functionalization with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, whereas the products formed by quenching IIIb/IVb with electrophiles retain nucleophilic character at phosphorus (implying that further derivatization requires as well electrophilic reagents), the substituents in Ib/IIb impose electrophilic character on the P-atom in a resulting phosphine and make Ib/ IIb reagents that can decorate an electrophilic substrate with an electrophilic R 2 P-fragment allowing for post-functionalization with nucleophiles. [3,4] In this respect, the reactivity of both classes of phosphide reagents can be considered as complementary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations